BERCEUSES DU CHAT BY IGOR STRAVINSKY - Răzvan METEA (Studia Universitatis Babeş-Bolyai. Musica)
Berceuses du chat by Igor Stravinsky. Berceuses du chat by Igor Stravinsky for voice and clarinet trio - picollo clarinet, clarinet in A, bass clarinet - is a cycle of four vocal-instrumental miniatures that are part of the Russian period of the composer’s work, being completed in 1915-1916. The timbral balance achieved between the voice and the instrumental ensemble, the lyrical manner of musical expression, the specific rhythmic-melodic typologies of writing, the chromatic versus diatonic dichotomy, the affiliation of the opuses to the comic aesthetic category are characteristics of this series of four micro-art-songs, cradle songs, dedicated to and apparently describing the characteristics of a cat.